Smaller dishware to reduce energy intake: fact or fiction? - Dana Lee Olstad; Clare Collins (BMC, 2019)
Abstract The potential effects of dishware size on energy intake are unclear, as many previous studies have been of low methodological quality. A newly published paper by Kosīte et al. (IJBNPA 10.1186/s12966-019-0826-1, 2019) reports findings from a rigorous, pre-registered investigation of the effects of manipulating plate size on total energy intake within a single eating occasion. This Editorial considers the implications of these new findings in light of previous evidence pertaining to the efficacy of behavioral nudges in particular, and in relation to contextual drivers of food consumption more generally. We conclude that the potential impact of behavioral nudges may have been exaggerated in the past, and call for future high-quality randomized controlled trials to establish whether reducing dishware size and other behavioral nudges might offer an effective complement to more comprehensive, multi-level interventions to reduce overconsumption of foods and beverages at a population-level.